(untitled) - DiGregorio, G. John (West Chester, PA, 1996)
The book attempts to present the most common trade names and adult doses, and should be used only as a guideline to these; it should not be considered as an official therapeutic document. If there is a discrepancy in therapeutic category, preparations, and dosages, the reader is advised to obtain official and more complete information from the pharmaceutical manufacturer.
Keywords: Drug therapy,Pharmaceutical preparations